Non-P450 aldehyde oxidizing enzymes: the aldehyde dehydrogenase superfamily - Marchitti, Satori A (2008)
BACKGROUND: Aldehydes are highly reactive molecules. While several non-P450 enzyme systems participate in their metabolism, one of the most important is the aldehyde dehydrogenase (ALDH) superfamily, composed of NAD(P)(+)-dependent enzymes that catalyze aldehyde oxidation. OBJECTIVE: This article presents a review of what is currently known about each member of the human ALDH superfamily including the pathophysiological significance of these enzymes. METHODS: Relevant literature involving all members of the human ALDH family was extensively reviewed, with the primary focus on recent and novel findings. CONCLUSION: To date, 19 ALDH genes have been identified in the human genome and mutations in these genes and subsequent inborn errors in aldehyde metabolism are the molecular basis of several diseases, including Sjögren-Larsson syndrome, type II hyperprolinemia, γ-hydroxybutyric aciduria and pyridoxine-dependent seizures. ALDH enzymes also play important roles in embryogenesis and development, neurotransmission, oxidative stress and cancer. Finally, ALDH enzymes display multiple catalytic and non-catalytic functions including ester hydrolysis, antioxidant properties, xenobiotic bioactivation and UV light absorption.